Development of Globalization in Culture on The Example of Europe - Monika HADAŚ-DYDUCH; Sebastian WILCZEWSKI (Communications of International Proceedings, 2021)
This article attempts to reflect on the consequences of cultural globalization, i.e. the opportunities and threats that exist it brings with it for existing local cultures. As we know, The processes of globalization contribute to the emergence of many, often contradictory phenomena in the field of culture, which influence the existing local cultural systems in various ways. It is assumed that the most important consequence of cultural globalization is the increased contact of different cultures, thanks to which certain cultural elements are mixed, disseminated and sometimes made similar. The study was based on the countries belonging to Europe. The aim of the study is to identify countries most similar to Poland in the development of cultural globalization. The study used an algorithm based on the wavelet transform and DTW. The DTW algorithm was used in the study because it is extremely effective in measuring the similarity of signals in the time domain. It minimizes the effects of shifting and distorting signals through "flexible" transformation of the time signal, which allows you to find similar shapes with different phases.
Keywords: Globalization; internationalization; wavelets; cultural globalization.